2013
DOI: 10.1016/j.taap.2013.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition during oncogenic transformation induced by hexavalent chromium involves reactive oxygen species-dependent mechanism in lung epithelial cells

Abstract: Hexavalent Chromium [Cr(VI)] is an important human carcinogen associated with pulmonary diseases and lung cancer. Exposure to Cr(VI) induces DNA damage, cell morphological change and malignant transformation in human lung epithelial cells. Despite extensive studies, the molecular mechanisms remain elusive, it is also not known if Cr(VI)-induced transformation might accompany with invasive properties to facilitate metastasis. We aimed to study Cr(VI)-induced epithelial–mesenchymal transition (EMT) and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…The mRNA expression of PCNA and cyclin D1 in skin samples was determined using real-time quantitative PCR with a Bio-Rad MyiQ thermocycler and SYBR green detection system (Bio-Rad, CA), as described previously (Ding et al 2013; Pratheeshkumar et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…The mRNA expression of PCNA and cyclin D1 in skin samples was determined using real-time quantitative PCR with a Bio-Rad MyiQ thermocycler and SYBR green detection system (Bio-Rad, CA), as described previously (Ding et al 2013; Pratheeshkumar et al 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Exposure to Cr(VI) induces DNA damage, cell morphological changes and malignant transformation in human lung epithelial cells (Ding et al , 2013). Epidemiological studies have reported that the lung cancer morbidity rate is 20 times higher in ex-chromate workers than for non-smokers (Nakagawa et al , 1984).…”
Section: Introductionmentioning
confidence: 99%
“…32 In the same way, chromium-induced EMT is dependent on intracellular ROS in lung epithelial cells. 33 A specialized EMT process is the endothelial-to-mesenchymal transition (EndMT). By means of the EndMT, ECs become myofibroblasts.…”
mentioning
confidence: 99%